GAYA BAHASA DALAM NOVEL MARYAMAH KARPOV KARYA ANDREA HIRATA - Sinaga, Mangatur Sinaga; Nurfadila, Nurfadila; Syafrial, Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: The research this discusses about the style of language in the novel Maryamah Karpov by Andrea Hirata and discuss the overall style of language in the novel Maryamah Karpov by Andrea Hirata and discuss the overall style of the exiting language in the novel novel Maryamah Karpov by Andrea Hirata. This research used a qualitative approach and descriptive method that aims to describe any style of language used in the novel novel Maryamah Karpov by Andrea Hirata. In addition, this research also discusses the meaning is in a style that is found on the novel novel Maryamah Karpov by Andrea Hirata. The results of this research also as a form of documentation style that exists in novel novel Maryamah Karpov by Andrea Hirata.Keywords: language style , novel novel Maryamah Karpov by Andrea Hirata